2004
DOI: 10.4315/0362-028x-67.11.2465
|View full text |Cite
|
Sign up to set email alerts
|

Control of Growth and Survival of Listeria monocytogenes on Smoked Salmon by Combined Potassium Lactate and Sodium Diacetate and Freezing Stress during Refrigeration and Frozen Storage

Abstract: In this study, we evaluated the antimicrobial effects of different levels of a potassium lactate (PL) plus sodium diacetate (SDA) mixture against the growth and survival of Listeria monocytogenes Scott A inoculated onto smoked salmon stored at 4, 10, and -20 degrees C. The effect of freezing stress on the growth kinetics of L. monocytogenes Scott A on smoked salmon at 4 and 10 degrees C was also investigated. The use of PL+SDA at all tested levels (1.5, 3.3, and 5% of a 60% commercial solution of PURASAL P Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 31 publications
6
32
0
Order By: Relevance
“…While our study does not encompass all possible variations in inoculum level, medium preparation, and competitive microbes found on some naturally contaminated products, data from previous studies indicate that what we found was not unusual. Consistent with our results, studies with lower inoculum levels also found similar growth rates (e.g., 0.37 log units/day) and similar final concentrations (e.g., ϳ8 log CFU/ml) for L. monocytogenes on vacuumpacked CSS at refrigerated temperatures (e.g., 4°C) (7,70). Our results do provide insights into the relative differences in transcriptomes of L. monocytogenes at the same growth phase under different complex conditions and reflect the gene expression pro-…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While our study does not encompass all possible variations in inoculum level, medium preparation, and competitive microbes found on some naturally contaminated products, data from previous studies indicate that what we found was not unusual. Consistent with our results, studies with lower inoculum levels also found similar growth rates (e.g., 0.37 log units/day) and similar final concentrations (e.g., ϳ8 log CFU/ml) for L. monocytogenes on vacuumpacked CSS at refrigerated temperatures (e.g., 4°C) (7,70). Our results do provide insights into the relative differences in transcriptomes of L. monocytogenes at the same growth phase under different complex conditions and reflect the gene expression pro-…”
Section: Discussionsupporting
confidence: 78%
“…This pathogen is of particular concern to the ready-to-eat (RTE) meat and seafood industries due to its ability to grow at temperatures as low as Ϫ0.4°C and under conditions of salt content as high as 25% (at 4°C) (1)(2)(3). Cold smoked salmon (CSS), an RTE seafood, represents a typical food product that can support the growth of L. monocytogenes from low numbers to potentially hazardous levels (4)(5)(6)(7)(8)(9). The heat treatment applied during processing of CSS is not sufficient to inactivate microbes present on the raw material, including L. monocytogenes (10,11).…”
mentioning
confidence: 99%
“…Moreover, in a similar study performed on smoked salmon results showed that L. monocytogenes subjected to 5 days freeze stress and then stored at 4°C for 30 days presented a retarded lag time (18 days) compared with control samples (8 days). These authors also showed that an additional treatment with a combination of potassium lactate and sodium diacetate can be more inhibitory in frozen than in unfrozen smoked salmon (Yoon et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, the largest multi-state outbreaks of listeriosis have been due to contaminated RTE foods, including outbreaks from Mexican style cheese (142 cases), frankfurters (108 cases), and cantaloupe (147 cases) (Centers for Disease and Prevention, 2013). Thus, there are a number of treatments currently employed using either physical or chemical means of decontamination (Aymerich et al, 2008;Beuchat and Brackett, 1990;Gunes et al, 2012;Islam et al, 2002;Yoon et al, 2004). These methods vary in their efficacy and also tend to be fairly broadespectrum; i.e., they kill all bacteria present in the foods, a majority of which are beneficial e which reduces the nutritional/health value of the foods.…”
Section: Introductionmentioning
confidence: 98%